Nature’s Perfection: Aristotle and Descartes on Motion and Purpose - Humphreys, Justin (Conatus - Journal of Philosophy, 2021)
Descartes holds that, insofar as nature is a purposeless, unthinking, extended substance, there could be no final causes in physics. Descartes’ derivation of his three laws of motion from the perfections of God thus underwrites a rejection of Aristotle’s conception of natural self-motion and teleology. Aristotle derived his conception of the purposeful action of sublunar creatures from his notion that superlunar bodies are perfect, eternal, living beings, via the thesis that circular motion is more complete or perfect than rectilinear motion. Descartes’ reduction of circular motion to rectilinear motion, achieved through his theological foundation of the laws of motion, thus marks a crucial break from Aristotle’s philosophy of nature. This paper argues that the shift from the Aristotelian conception of nature as self-moving and teleological to the Cartesian conception of nature as purposeless and inert, is not an empirical discovery but is rooted in differing conceptions of where perfection lies in nature.